Barriers and Prompts to Parent-Child Sexual Communication. Issue 3 (2nd July 2016) - Pariera, Katrina L.
ABSTRACT: One key resource for improving sexual health outcomes for young people is parent-child sexual communication, but researchers have yet to explore what prompts these conversations, and detailed research into the barriers of these conversations is lacking. This study aims to explicate what prompts these conversations and what prevents them from happening more often. A nationally representative, random sample of U.S. mothers and fathers was surveyed ( N = 186). Participants reported that thinking their child is too young, regardless of the child's age, was a major communication barrier, while communication self-efficacy and perceived value in sexual communication were associated with more communication. Sexual communication was often prompted by the child, or the parent deciding the child was "old enough, " and was rarely prompted by a family member or healthcare provider. Implications for improving parent-child sexual communication are discussed.